1996
DOI: 10.1117/12.246716
|View full text |Cite
|
Sign up to set email alerts
|

<title>Design and construction of a coherent light pupil imaging Stokes polarimeter for 1315 nm</title>

Abstract: An imaging polarimeter has been designed and constructed at the Air Force Phillips Laboratories to measure the polarization properties of laser speckle patterns. An imaging polarimeter spatially measures the polarization state of light coming from an object, thereby producing a "polarization image". The system described was designed to image the pupil of an optical system containing speckle patterns created by illumination of diffuse objects with light from a pulsed 1315 nm laser. Difficulties encountered due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Experience has shown that adhesives used in cubes must closely match the index of refraction of the cube material, or fringe patterns are created by the glue/glass and glue/coating interfaces. 7 Coherent imaging systems are also particularly sensitive to dust and surface defects. Diffracted light from dust particles, surface defects and glue or glass inhomogeneities, create diffraction patterns that can spread out and degrade large areas of data.…”
Section: Coherent Imaging System Design Considerationsmentioning
confidence: 99%
“…Experience has shown that adhesives used in cubes must closely match the index of refraction of the cube material, or fringe patterns are created by the glue/glass and glue/coating interfaces. 7 Coherent imaging systems are also particularly sensitive to dust and surface defects. Diffracted light from dust particles, surface defects and glue or glass inhomogeneities, create diffraction patterns that can spread out and degrade large areas of data.…”
Section: Coherent Imaging System Design Considerationsmentioning
confidence: 99%
“…The polarimeter decomposes the input polarized light onto four channels whose respective intensity is measured by a photon counting camera. The intensity measurement made on each of the four detectors is denoted by the matrix I written as 10 1= (2) 13 where the spatially integrated intensity for each channel is ii = I I(x)WA(x) d2x (3) A is the area of the detector and WA (x) is the detector active area window function. The intensities are obtained from I = P S, where the input Stokes vector, S, having the units of tA limitation, however, is that an optical element that coherently combines two beams cannot be represented by a Mueller matrix.…”
Section: Introductionmentioning
confidence: 99%